If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 1x Reorder the terms: -2 + 4x = 1x Solving -2 + 4x = 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + 4x + -1x = 1x + -1x Combine like terms: 4x + -1x = 3x -2 + 3x = 1x + -1x Combine like terms: 1x + -1x = 0 -2 + 3x = 0 Add '2' to each side of the equation. -2 + 2 + 3x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 0 + 2 3x = 0 + 2 Combine like terms: 0 + 2 = 2 3x = 2 Divide each side by '3'. x = 0.6666666667 Simplifying x = 0.6666666667
| 0.8y-11=1.6y-15 | | 4(2+3x)= | | x/-3.2-19 | | x+20x=72 | | p^2=-6 | | 3-(12-m)=-1(m-8) | | 7(3c+1)=5c-2(c+3) | | 15=-3(a+2)+3a | | y=7.50+2.50 | | 2n(1)=1.30 | | 3-x+11=10 | | 3x(6)=3.90 | | 2(3x-1)+5y=53 | | 6-y=0 | | 4(17.3)= | | 8(2-p)=24 | | 3+2i=0 | | -3x-(3x)=-24 | | 10x^2+3=-143 | | 12-36x= | | 100x+75= | | 6(2c+7)=3c-2(c+9) | | 8r+5(7r-1)=-134 | | 2x^2+8x=60 | | (3x-1)+5y=53 | | 162=(x-8)+(x+2) | | x+(x+2)+(X+4)=x+x+2+x+4 | | -8(3x+6)=144 | | 20x-16= | | 3x/2-5=x/3-7 | | -2(8k-4)=104 | | 1/9=r/0.3 |